WHEN ORGANIZATIONS MATTER. (29th December 2014) - Ebert, Kim; Estrada, Emily P.; Lore, Michelle Halla
Abstract Increasingly, scholars have argued that immigration politics are inseparable from racial politics, which implies that organizations and individuals who mobilize around racial group interests influence racial and immigration attitudes and behaviors. How does the racial-political context influence anti-immigration lawmaking? In what ways does this influence vary at different stages of lawmaking? To address these questions, we combine comprehensive datasets of racially conservative organizations and state immigrant legislation and use negative binomial regression to estimate the count of anti-immigrant bills and laws in the fifty states from 1991 to 2010. We find that the presence of racially conservative organizations encourages the introduction of exclusionary proposals, but only in contexts with a Republican-dominated government. At the approval stage, on the other hand, racially conservative organizations foster the passage of exclusionary laws, and this effect is heightened in contexts with a growing foreign-born population or where a majority of voters report anti-immigrant opinions or identify as conservative. This indicates that the institutionalization of the colorblind racial ideology (in the form of racially conservative organizations) resonates with lawmakers, but in a different manner when the stakes are higher. These findings have important implications and challenge previous research on the conditions under which advocacy organizations influence lawmaking and additional forms of group behavior.